Nucleotide sequence of cytoplasmic initiator tRNA from Tetrahymena thermophila. - Kuchino, Y (1981)
The total primary structure of cytoplasmic initiator tRNA from Tetrahymena thermophila mating type IV, was determined by post labeling techniques. The sequence is pa-G-C-A-G-G-G-U-m1G-G-C-G-A-A-A-D-Gm-G-A-A-U-C-G-C-G-U-Psi-G-G-G-C-U-C-A-U-t6A -A-C-Psi-C-A-A-A-A-m7G-U-m5C-A-G-A-G-G-A-Psi-C-G-m1A-A-A-C-C-U-C-U-C-U-C-U-G-C- U-A-C-C-AOH. The nucleotide residue in the position next to the 5'-end of the anticodon of this tRNA (residue No. 33) is uridine instead of cytidine, which has been found in cytoplasmic initiator tRNAs from multicellular eukaryotic organisms. The sequence of three consecutive G-C base pairs in the anticodon stem common to all other cytoplasmic initiator tRNAs is disrupted in this tRNA; namely, the cytidine at residue 40 in this region is replaced by pseudouridine in Tetrahymena initiator tRNA.